2022
DOI: 10.1017/jfm.2022.574
|View full text |Cite
|
Sign up to set email alerts
|

Direct numerical simulation of supersonic and hypersonic turbulent boundary layers at moderate-high Reynolds numbers and isothermal wall condition

Abstract: We study the structure of high-speed zero-pressure-gradient turbulent boundary layers up to friction Reynolds number $Re_{\tau } \approx 2000$ using direct numerical simulation of the Navier–Stokes equations. Both supersonic and hypersonic conditions with nominal free-stream Mach numbers $M_{\infty }=2$ , $M_{\infty }=5.86$ and heat transfer at the wall are considered. The present simulations extend the database currently availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 60 publications
15
47
0
Order By: Relevance
“…In fact, the multi-physics coupling is more prominent in compressible wall turbulence than incompressible flows to some extent. For example, very recently, several studies have reported that the alterations of the wall thermal boundary condition can remarkably modify the temperature and velocity streaks in supersonic/hypersonic turbulent boundary layers (Hirai et al 2021;Cogo et al 2022;Huang et al 2022). Hence, the present study can provide an effective tool to quantify these variations.…”
Section: Discussionmentioning
confidence: 70%
“…In fact, the multi-physics coupling is more prominent in compressible wall turbulence than incompressible flows to some extent. For example, very recently, several studies have reported that the alterations of the wall thermal boundary condition can remarkably modify the temperature and velocity streaks in supersonic/hypersonic turbulent boundary layers (Hirai et al 2021;Cogo et al 2022;Huang et al 2022). Hence, the present study can provide an effective tool to quantify these variations.…”
Section: Discussionmentioning
confidence: 70%
“…2018) and from DNS of the energy spectrum at different (Modesti & Pirozzoli 2016; Yao & Hussain 2020; Cogo et al. 2022; Cheng & Fu 2022 b ). As discussed in figure 6, the large-scale structure corresponding to the outer peak results mainly from the kinematic part of the forcing, not the thermodynamic part.…”
Section: Resultsmentioning
confidence: 99%
“…A similar interpretation is provided in [32], which cites results from [33]: "[...]which argued that the excess of turbulent production in the log layer feeds inactive motions that do not contribute to the turbulent shear stress, but transfer energy to other locations of the flow. ".…”
Section: Physical Mechanismmentioning
confidence: 60%